Sociodemographic and gender determinants of late-life suicide in users and non-users of antidepressants - Hedna, Khedidja (Eur J Public Health, 2020)
BACKGROUND: The treatment of depression is a main strategy for suicide prevention in older adults. Our aim was to examine factors related to suicide in older adults (75+) with and without antidepressant (AD) therapy. METHODS: A national population-based register study, including all Swedish residents aged ≥75 years between 2006 and 2014 (N = 1 413 806). A nested case–control design was used to investigate sociodemographic factors associated with suicide among users and non-users of ADs. Risk estimates were calculated in adjusted conditional logistic regression models for the entire cohort and by gender. RESULTS: In all, 1305 individuals died by suicide (70% men). The suicide rate in men who used ADs was over four times higher than women with such treatment. Being unmarried was a risk factor for suicide in men but not in women. Being born outside of Nordic countries was associated with increased suicide risk; a 3-fold risk increase was observed in non-Nordic women without AD treatment. Lower suicide risk was observed in blue-collar women who used ADs, whereas a higher risk was found in blue-collar men who did not. CONCLUSIONS: Our differential findings on factors associated with suicide can offer clues for gender-specific preventive strategies that go beyond the healthcare sphere.